Increased remission with fewer corticosteroids and more biologics in rheumatoid arthritis at 7-year follow-up in real-life conditions - Guillaume Larid; Justine Vix; Ronan Garlantezec; Elodie Loppin; Elisabeth Gervais (Scientific Reports, 2022)
Abstract Remission in rheumatoid arthritis (RA) is an important therapeutic target that is not easy to achieve in real-life conditions. Some prognostic factors have been identified but the literature is variable. The objectives of this study were to evaluate the remission rate and the maintenance of remission in patients with RA over 7 years of follow-up in real-life conditions and to identify prognostic factors of long-term remission. Patients with RA seen at the Poitiers University Hospital were identified and clinical and biological data were collected. Data were analysed after 1 year and 7 years. Twice as many patients were in remission at 7 years than at 1 year of follow-up. 48.6% of patients who were not in remission at 1 year obtained remission at 7 years of follow-up. Patients achieving remission were more often receiving coprescription of csDMARDs and bDMARDs. Patients not in remission at 7 years were given more corticosteroids at higher doses. After 7 years of follow-up, low initial disease activity and use of csDMARDs and bDMARDs appeared to be independent positive predictive factors. Once obtained at one year, remission was maintained for 76% of our patients. As a conclusion, modern management of RA, whatever disease duration, leads to remission rates similar to those of early RA after 7 years of follow-up.